Reactions and feelings of health professionals in the care of hospitalized patients with suspected covid-19 - Ana Claudia Ramos De Paula; Aline Graziela Deneka Carletto; Daniele Lopes; Joabe Candido Ferreira; Nelsi Salete Tonini; Sara Priscila Carvalho Trecossi
ABSTRACT Objective: To understand the reactions and feelings of professionals in the frontline of care for inpatients with suspected COVID-19. Method: Qualitative approach study with 19 health team professionals from a teaching hospital located in the hinterland of the state of Paraná. Data were collected in March and April 2020. For data analysis, content analysis was used. Results: Of all professionals, 89.5% were female, 57.8% were between 20 and 30 years old. The following emotions and feelings were highlighted by the content analysis: Motivation; willingness to contribute; feelings of fear, anxiety; obligation; preoccupation with death; sadness; discrimination; isolation; prejudice; uncertainty; and doubts about the future. Conclusion: The research showed workers' reactions/feelings, which were ambivalent both as a motivating impulse and as self-care, such as in the case of isolation/fear in coping with COVID-19.